Evaluation of modified nasal to oral endotracheal tube switch-For modified alar base cinching after maxillary orthognathic surgery - Taj Nizam Shakeel Shaik; Sridhar Meka; Pavan Kumar Ch; Naga Neelima Devi Kolli; P. Srinivas Chakravarthi; Vivekanand S. Kattimani; Krishna Prasad L. (Elsevier, 2017)
Background: Soft tissue changes secondary to Maxillary orthognathic surgery are many fold. The alar flare is one among them, which affects the appearance of the patient. Cinch suture has been used to prevent alar flare; but the presence of anaesthetic tube hinders cinching. So, the study was aimed to assess an efficacy of modified nasal to oral tube switch technique for modified alar cinching to prevent alar flare after orthognathic and nasal corrective surgeries. Materials and methods: Patients were randomly allocated in each group, who underwent modified alar base cinching with and without nasal to oral tube switch. Changes in alar base width, upper lip length was measured with Digital Vernier Caliper and nasolabial angle (Cotg-Sn-Ls) on lateral cephalogram at 1st, 3rd, 6th, and 12th months after surgery. The time taken and ease of tube switch were noted. The data obtained were tabulated and interpreted using a test of significance. Results: Study results showed no statistical significant difference in perinasal soft changes among both groups. But tube switch appears to be beneficial to prevent alar flare. Conclusion: Modified alar base cinching was performed effectively in patients with a modified tube switch technique. It increased positive results in comparison with non-shift. The technique of tube switch used is effective in prevention of alar flare. Because of small sample size and limited period of follow up, our study suggests multi centre, randomized studies to know the technical difficulties of tube switch for cinching and aesthetic results with varying anaesthetist and the surgeon's experience.